2013
DOI: 10.3126/njms.v2i2.8942
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Congenital Heart Disease in Neonate in a Tertiary Level Hospital

Abstract: Background: Congenital heart disease (CHD) has already been recognized as one of the important cause of neonatal mortality and morbidity. The reported prevalence of CHD in live newborns tends to vary a lot due to various unrecognizable lesions at birth and lack of technical expertise. Methods: A cross sectional study was carried out in the department of Neonatology at Mymensingh Medical College Hospital (MMCH), Bangladesh from January to December 2010 to find prevalence of CHD in neonates. Results: Out of 6560… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 9 publications
4
16
1
Order By: Relevance
“…Islam MN et al showed the associated non-cardiac anomalies. 15 Down's syndrome was noticed in 6% cases, polydactyly and syndactyly were detected in 4% newborn. Cleft lip with palate, cataract and renal anomaly were also found in 2% cases respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Islam MN et al showed the associated non-cardiac anomalies. 15 Down's syndrome was noticed in 6% cases, polydactyly and syndactyly were detected in 4% newborn. Cleft lip with palate, cataract and renal anomaly were also found in 2% cases respectively.…”
Section: Discussionmentioning
confidence: 99%
“…15 Among simple CHD, VSD was the commonest followed by ASD then PDA & TOF. Among Complex CHD, TGA with shunt were common.…”
Section: Discussionmentioning
confidence: 99%
“…Asian race is found to be more affected than non-Asian race due to high rate of consanguineous marriages. 6 But in Bangladesh, only a few study was to evaluate. A cross sectional study found that the prevalence rate of CHD in neonates is about 7.8/1000 live births.…”
Section: Introductionmentioning
confidence: 99%
“…A cross sectional study found that the prevalence rate of CHD in neonates is about 7.8/1000 live births. 6,7 Maximum neonates remain asymptomatic during neonatal period. This study found that approximately 50-70% of neonates having clinical murmur remain asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…Two hospital based study findings are suggestive of variable prevalence of congenital heart disease (7.8 and 25/1000 live births respectively) among Bangladeshi population which mandated to carry out heart defects related documentation. 6,7 Contemporary routine screening for congenital heart disease depends on a mid-trimester anomaly scan, involving imaging of the heart chambers, and a postnatal cardiovascular system examination. 8 The sensitivity of CHD detection by anomaly scan is highly variable, depending on operator expertise, gestational age, fetal position, and the type of cardiac defect.…”
Section: Introductionmentioning
confidence: 99%